Myocardial improvement with human embryonic stem cell-derived cardiomyocytes enriched by p38MAPK inhibition - YEGHIAZARIANS, YEREM (2011)
BACKGROUND AIMS: We have shown previously that inhibition of the p38 mitogen-activated protein kinase (p38MAPK) directs the differentiation of human embryonic stem cell (hESC)-derived cardiomyocytes (hCM). We investigated the therapeutic benefits of intramyocardial injection of hCM differentiated from hESC by p38MAPK inhibition using closed-chest ultrasound-guided injection at a clinically relevant time post-myocardial infarction (MI) in a mouse model. METHODS: MI was induced in mice and the animals treated at day 3 with: (a) hCM, (b) human fetal fibroblasts (hFF) as cell control, or (c) medium control (n = 10 animals/group). Left ventricular ejection fraction (LVEF) was evaluated post-MI prior to therapy, and at days 28 and 60 post-cell therapy. Hearts were analyzed at day 60 for infarct size, angiogenesis, cell fate and teratoma formation. RESULTS: LVEF was improved in the hCM-treated animals compared with both hFF and medium control-treated animals at day 28 (39.03 ± 1.79% versus 27.89 ± 1.27%, P < 0.05, versus 32.90 ± 1.46%, P < 0.05, respectively), with sustained benefit until day 60. hCM therapy resulted in significantly smaller scar size, increased capillary bed area, increased number of arterioles, less native cardiomyocyte (CM) apoptosis, and increased CM proliferation compared with the other two groups. These benefits were achieved despite a very low retention rate of the injected cells at day 60, as assessed by immunohistochemistry and quantitative real-time polymerase chain reaction (qPCR). Therapy with hCM did not result in intramyocardial teratoma formation at day 60. CONCLUSIONS: This study demonstrates that hCM derived from p38MAPK-treated hESC have encouraging therapeutic potential.